Manajemen Pengawas Sekolah Dasar pada Masa Pandemi Covid-19 - Juliana Juliana; Yusrizal Yusrizal; Niswanto Niswanto (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2021)
Abstract: During the COVID-19 pandemic, the presence of a supervisor is essential, especially in providing guidance and supervision, conducting evaluations, providing teacher professional training to increase the effectiveness of the learning process during the Covid-19 pandemic. Given the importance of the supervisory role, the ministry of education has issued technical guidelines for implementing supervision during the covid-19 pandemic. This article aims to describe the management of the elementary school supervisor during the covid-19 pandemic in Pidie Regency. The qualitative method with a descriptive model was used in this research, and data was obtained from observations, interviews, and relevant literature reviews. This study found that the supervisors of elementary school had not prepared the supervision program properly. Likewise, the implementation and evaluation are not following the supervisor’s manual and technical instructions for the supervisor during the COVID-19 pandemic. As a result, the supervision does not positively impact effective learning during the COVID-19 pandemic at elementary schools in Pidie Regency.Abstrak: Di masa pandemi COVID-19, kehadiran seorang pengawas sangat penting, terutama dalam memberikan bimbingan dan supervisi, melakukan evaluasi, memberikan pelatihan profesional guru untuk meningkatkan efektivitas proses pembelajaran selama pandemi Covid-19. Mengingat pentingnya peran pengawas, Kemendikbud telah menerbitkan pedoman teknis pelaksanaan pengawasan selama pandemi Covid-19. Artikel ini bertujuan untuk mendeskripsikan manajemen pengawas sekolah dasar pada masa pandemi covid-19 di Kabupaten Pidie. Metode kualitatif dengan model deskriptif digunakan dalam penelitian ini, dan data diperoleh dari observasi, wawancara, dan studi pustaka yang relevan. Penelitian ini menemukan bahwa pengawas sekolah dasar belum mempersiapkan program supervisi dengan baik. Demikian pula, pelaksanaan dan evaluasinya tidak mengikuti pedoman dan petunjuk teknis pengawas masa pandemi COVID-19. Akibatnya, pengawasan yang dilakukan tidak berdampak positif terhadap pembelajaran yang efektif selama pandemi COVID-19 di sekolah dasar di Kabupaten Pidie.